Remyelination and ageing: Reversing the ravages of time. (December 2019) - Neumann, Bjoern; Segel, Michael; Chalut, Kevin J; Franklin, Robin JM
Remyelination is a neuroprotective regenerative response to demyelination that restores saltatory conduction and decreases the vulnerability of axons to irreversible degeneration. It is a highly efficient process: however, as with all regenerative processes, its efficiency declines with ageing. Here we argue that this age-related decline in remyelination has a major impact on the natural history of multiple sclerosis (MS), a disease often of several decades' duration. We describe recent work on (1) how ageing changes the function of oligodendrocyte progenitor cells (OPCs), the cells primarily responsible for generating new myelin-forming oligodendrocytes in remyelination, (2) how these changes are induced by age-related changes in the OPC niche and (3) how these changes can be reversed, thereby opening up the possibility of therapeutically maintaining remyelination efficiency throughout the disease, preserving axonal health and treating the progressive phase of MS.